2011
DOI: 10.1186/1471-2148-11-102
|View full text |Cite
|
Sign up to set email alerts
|

The sequence, structure and evolutionary features of HOTAIR in mammals

Abstract: BackgroundAn increasing number of long noncoding RNAs (lncRNAs) have been identified recently. Different from all the others that function in cis to regulate local gene expression, the newly identified HOTAIR is located between HoxC11 and HoxC12 in the human genome and regulates HoxD expression in multiple tissues. Like the well-characterised lncRNA Xist, HOTAIR binds to polycomb proteins to methylate histones at multiple HoxD loci, but unlike Xist, many details of its structure and function, as well as the tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
103
0
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(112 citation statements)
references
References 66 publications
6
103
0
3
Order By: Relevance
“…The pair-wise conservation atlases of each chromosome for human lncRNA genes also exhibit the same pattern ( Figure 2b; Figure S5). Consistent with the reported studies [39,40], hotair were found widely existing in mammals, as shown by the CPCC score in PhyloNONCODE ( Figure S11), and the xist gene existing from humans to the opossum, absent in the platypus and chicken ( Figure S11). 62% and 59% of human lncRNAs were found to be 1 : 1 orthologous in mouse and rat with CPCC score in 0 to 1, similar to a study of human long non-coding RNAs in the other six mammals, in which the figures are 58% and 54% [26].…”
Section: Conservation Study Of Lncrnas In Mammalssupporting
confidence: 78%
“…The pair-wise conservation atlases of each chromosome for human lncRNA genes also exhibit the same pattern ( Figure 2b; Figure S5). Consistent with the reported studies [39,40], hotair were found widely existing in mammals, as shown by the CPCC score in PhyloNONCODE ( Figure S11), and the xist gene existing from humans to the opossum, absent in the platypus and chicken ( Figure S11). 62% and 59% of human lncRNAs were found to be 1 : 1 orthologous in mouse and rat with CPCC score in 0 to 1, similar to a study of human long non-coding RNAs in the other six mammals, in which the figures are 58% and 54% [26].…”
Section: Conservation Study Of Lncrnas In Mammalssupporting
confidence: 78%
“…10Y12 lncRNAs have also been related to many diverse biological processes, such as cell cycle, cell proliferation, cell apoptosis, and cell differentiation. 17Y19 On the basis of the pattern of their functions, lncRNAs have been divided into 4 subtypes, namely, signals (X-inactive specific transcript [XIST] 20 and PANDA 21 ), decoys (Gas5 21 ), guides (HOX transcript antisense intergenic RNA [HOTAIR] 22 and lincRNA-p21 23 ), and scaffolds (Anril 24 ). Previous studies have found that the abnormal expression or dysfunction of lnRNA is closely related to the initiation and progression of human diseases, including cancer.…”
Section: Lncrnamentioning
confidence: 99%
“…23,24 The human HOX gene family is divided into 4 subfamilies: HOXA, HOXB, HOXC, and HOXD, whereas LncRNA HOTAIR is identified from a custom tilling array of the HOXC locus. 25,26 HOTAIR is located in the antisense strand of the HOXC gene cluster, but it could regulate the HOXD gene cluster.…”
Section: Hotairmentioning
confidence: 99%
“…Structure prediction vertified that the sequences and structures of the 5' end exon 1 and the 3' end domain B of exon 6 were highly conserved in mammals. It is considered that the two domains are the functional domains of HOTAIR, which can interact with polycomb protein and play a wide range of biological functions [54].…”
Section: Hox Transcript Antisense Rnamentioning
confidence: 99%